Recent Consanguinity and Outbred Autozygosity Are Associated With Increased Risk of Late-Onset Alzheimer’s Disease - Napolioni, Valerio; Scelsi, Marzia A.; Khan, Raiyan R.; Altmann, Andre; Greicius, Michael D. (Frontiers in Genetics, 2021)
Prior work in late-onset Alzheimer’s disease (LOAD) has resulted in discrepant findings as to whether recent consanguinity and outbred autozygosity are associated with LOAD risk. In the current study, we tested the association between consanguinity and outbred autozygosity with LOAD in the largest such analysis to date, in which twenty LOAD GWAS datasets were retrieved through public databases. Our analyses were restricted to 8 distinct ethnic groups: African-Caribbean, Ashkenazi-Jewish European, European-Caribbean, French-Canadian, Finnish European, North-Western European, South-Eastern European, and Yoruba African for a total of 21,492 unrelated subjects (11,196 LOAD and 10,296 controls). Recent consanguinity determination was performed using FSuite v1.0.3, according to subjects’ ancestral background. The level of autozygosity in the outbred population was assessed by calculating inbreeding estimates based on the proportion (FROH) and the number (NROH) of Runs of Homozygosity (ROHs). We analyzed all eight ethnic groups using a fixed-effect meta-analysis, which showed a significant association of recent consanguinity with LOAD (N=21,481; OR=1.262, P=3.6x10-4), independently of APOE*4 (N=21,468, OR=1.237, P=0.002) and years of education (N=9,257; OR=1.274, P=0.020). Autozygosity in the outbred population was also associated with an increased risk of LOAD, both for FROH (N=20,237; OR=1.204, P=0.030) and NROH metrics (N=20,237; OR=1.019, P=0.006), independently of APOE*4 [(FROH, N=20,225; OR=1.222, P=0.029) (NROH, N=20,225; OR=1.019, P=0.007). By leveraging the Alzheimer’s Disease Sequencing Project (ADSP) whole-exome sequencing (WES) data, we determined that LOAD subjects do not show an enrichment of rare, risk-enhancing minor homozygote variants compared to the control population. A two-stage recessive GWAS using ADSP data from 201 consanguineous subjects in the discovery phase followed by validation in 10,469 subjects led to the identification of RPH3AL p.A303V (rs117190076) as a rare minor homozygote variant increasing the risk of LOAD [discovery: Genotype Relative Risk (GRR)=46, P=2.16x10-6; validation: GRR=1.9, P=8.0x10-4). These results confirm that recent consanguinity and autozygosity in the outbred population increase risk for LOAD. Subsequent work, with increased samples sizes of consanguineous subjects, should accelerate the discovery of non-additive genetic effects in LOAD.